Reproductive and Productive performances of Black Bengal Goats reared by the NGO Beneficiaries under semi intensive system in Bangladesh - Halim, MA; Kashem, MA; Mannan, A; Ahmed, SSU; Hossain, MA (International Journal of Natural Sciences, 2011)
The present study was carried out to investigate the reproductive and productive performances of Black Bengal goats reared by moderate and ultra-poor households at three different districts of Bangladesh during March, 2008 to June 2009. Two-stage stratified sampling procedures were applied for selection of farmers to conduct field base experiment. A total of 12 households from moderate poor and 12 from ultra- poor were selected purposively from selected NGO beneficiaries. Three separate ultra poor households were also selected for rearing of bucks for breeding of the does of the study areas. As a whole, 81 goats rearing households from 3 districts came under the study. The average (mean±SE) age at puberty, services per conception, gestation period, age at first kidding, post partum heat period and kidding interval were found to be 234.16±6.54 days, 1.22±0.25 numbers, 145.61±2.17 days, 361.83±11.29 days, 67.00±4.97days and 252.45±3.57days, respectively. The effect of herd size on age at first kidding was significant at P<0.05, whereas on age at puberty and kidding interval it was found significant at P<0.01. The average weight at puberty, weight of kids, weaning weight, litter size, milk yield/day, milk yield/lactation and lactation period were found to be 10.01±0.19kg, 0.93±0.03kg, 4.82±0.53kg, 1.68±0.001 numbers, 75.20±15.22 ml, 5.18±1.11 liters and 69.83±10.09 days, respectively. Body weight of goats at puberty and weaning weight of kids found to be significant among groups at p<0.05 whereas milk yield/day found to be significant at p<0.01. Thus, it could be recommend that the body weight at puberty, weaning weight, milk yield/day, age at first kidding, age at puberty and kidding interval of Black Bengal Goat have significant impact on rearing. Key words: Reproductive and productive traits; Black Bengal goat; moderate and ultra-poor households DOI: http://dx.doi.org/10.3329/ijns.v1i2.8819 International Journal of Natural Sciences (2011), 1(2):39-43